2019
DOI: 10.1371/journal.pone.0213681
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between muscle mass, strength and regional bone mineral density in young men

Abstract: Purpose Although the relationship between body composition and bone mineral density (BMD) is well established, the relative contribution of appendicular lean mass (ALM) and fat mass (FM) to BMD has been rarely evaluated in young men. Methods We assessed 100 young men (age: 24.4±2.8 years, BMI: 23.4±2.81 kg/m 2 ). Appendicular lean mass index (ALM/H 2 ) (ALMI), fat mass index (FM/ H 2 ) (FMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…In addition to age-and strain-related differences in skeletal morphology, we explored how changes in body composition (muscle, fat) and relevant biochemical markers relate to skeletal characteristics during development. In human studies, there is consensus that lean mass is positively associated with bone parameters [4][5][6][7]12]. Furthermore, some [8,10], albeit not all [9], studies, have shown that peak muscle mass precedes peak bone mass, further supporting the notion that muscle accrual impacts bone acquisition.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to age-and strain-related differences in skeletal morphology, we explored how changes in body composition (muscle, fat) and relevant biochemical markers relate to skeletal characteristics during development. In human studies, there is consensus that lean mass is positively associated with bone parameters [4][5][6][7]12]. Furthermore, some [8,10], albeit not all [9], studies, have shown that peak muscle mass precedes peak bone mass, further supporting the notion that muscle accrual impacts bone acquisition.…”
Section: Discussionmentioning
confidence: 95%
“…Among other modifiable factors, the relationship between body composition (muscle and fat mass) and bone during growth in humans has gained considerable interest [1,4]. Several pediatric studies suggest that muscle mass and bone mass are closely linked during development [4][5][6][7]. Less clear is, however, whether muscle development is driving skeletal development (mechanostat theory) and therefore, whether the attainment of peak muscle mass precedes the acquisition of peak bone mass [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a statistically significant relationship was found between Arms aBMD and Appendicular LSTMI, which remained significant even after adjusting for CF experience. LSTMI has been positively associated with aBMD at the WB- and regional levels in young men [ 25 , 26 ], indicating that increasing skeletal muscle mass may contribute to increased aBMD at the upper limb. The hypothesis that the non-weight bearing parts of the skeleton respond to CF participation in a dose-dependent manner deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest that muscle mass correlates with estimates of bone strength such as bone mineral density 3,4 . This relationship might be expected given that muscle is a primary source of mechanical stimuli for bone.…”
Section: Introductionmentioning
confidence: 97%